Free-form型机床的切齿优化（一）——优化模型的建立 - 张艳红; 郭九生; 王小椿 (Jixie chuandong)
In this paper, Free-form style machine tool setting parameters is analyzed, and a mathematical model of optimal synthesis is established. Keeping the predetermined second-order contact parameters unchanged and optimizing third-order contact, this model can meanwhjle optimize the forth-order contact parameters, improving quality of the meshing. Using projection on parameter line, the effectiveness of the algorithms is verified by computer simulation.